2013
DOI: 10.1107/s1744309113021246
|View full text |Cite
|
Sign up to set email alerts
|

Structure of isochorismate synthase DhbC fromBacillus anthracis

Abstract: The isochorismate synthase DhbC from Bacillus anthracis is essential for the biosynthesis of the siderophore bacillibactin by this pathogenic bacterium. The structure of the selenomethionine-substituted protein was determined to 2.4 Å resolution using single-wavelength anomalous diffraction. B. anthracis DhbC bears the strongest resemblance to the Escherichia coli isochorismate synthase EntC, which is involved in the biosynthesis of another siderophore, namely enterobactin. Both proteins adopt the characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The function and structure of asbB (Nusca et al, 2012), asbD (Schmelz et al, 2009) and asbF (Pfleger et al, 2008) in Petrobactin siderophore synthesis gene cluster have been investigated. Domagalski et al (2013) determined the crystal structure of different chorismic acid synthetase DhbC of Bacillibactin siderophore in Bacillus anthraci. DhbC participated in the biosynthesis of 2, 3-two hydroxybenzoate (DHB) and methyl naphthoquinone (MK) of the respiratory chain group; the consumption of DhbC led to the deficiency of DHB, which showed the importance of DhbC in siderophore biosynthesis (Domagalski et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The function and structure of asbB (Nusca et al, 2012), asbD (Schmelz et al, 2009) and asbF (Pfleger et al, 2008) in Petrobactin siderophore synthesis gene cluster have been investigated. Domagalski et al (2013) determined the crystal structure of different chorismic acid synthetase DhbC of Bacillibactin siderophore in Bacillus anthraci. DhbC participated in the biosynthesis of 2, 3-two hydroxybenzoate (DHB) and methyl naphthoquinone (MK) of the respiratory chain group; the consumption of DhbC led to the deficiency of DHB, which showed the importance of DhbC in siderophore biosynthesis (Domagalski et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Domagalski et al (2013) determined the crystal structure of different chorismic acid synthetase DhbC of Bacillibactin siderophore in Bacillus anthraci. DhbC participated in the biosynthesis of 2, 3-two hydroxybenzoate (DHB) and methyl naphthoquinone (MK) of the respiratory chain group; the consumption of DhbC led to the deficiency of DHB, which showed the importance of DhbC in siderophore biosynthesis (Domagalski et al, 2013). Hertlein et al (2014) studied the deletion of DhbF by gene inactivation mutagenesis and confirmed that dhb gene cluster was in charge of the synthesis of Bacillibactin siderophore (Hertlein et al, 2014).…”
Section: Resultsmentioning
confidence: 99%